Effects of some demographic factors on the prevalence and contagion transmitting of scabies in Al-Anbar province / Iraq - Wijdan Rabeea Al-Shaha; Sabah Ibrahim Al-Dulaimi (مجلة جامعة الانبار للعلوم الصرفة, 2015)
Scabies is one of the main contagious skin diseases which infect human skin epidermis and causes considerable damage all over the world, it is considered as a public health problem in Al-Anbar province population.This study depends on the analysis of recorder information in special document (questionnaire) prepared for this purpose and includes demographic factors such as gender, age , education, occupation , socioeconomic level , residence in prisons …. etc. Which affect disease prevalence and contagion transmitting from (413) scabies patient who were admitted to dermatology clinics in Al-Ramadi general hospital and Al-Falluja general hospital besides some private dermatological clinics in Falluja , Haditha and Rutba cities during the period ( October 2012 – up to the end of March 2013 ).Laboratory diagnosis were done in most scabies cases besides clinical diagnosis either by scraping method test or ink method test to isolate mite females and its eggs from mite burrows or lesions.The results of this study reveals that there is no significant difference between males and females in scabies infection which was (48.18 , 51.82)% respectively , the disease infects all body parts.The infection of disease occur in all months but there is considerable increasing in cold months ( December , October and November ) , the infection ratio was (21.79 , 18.64 , 15.25)% respectively.It reveals also that there is high infection in the age group (pre-school year) , (18-24) and (30-36) year which was (18.40 , 15.50 , 13.80)% respectively, it is found also that there is a decrease in disease infection with the increas of education level, the most ratio of infection is in low education levels ( primary school stage , uneducated level, kid stage) which is (37.29 , 20.10 , 18.40)% respectively.Significant differences are also found between scabies patients according to their occupation, there is a high infection in ( house wife , student , free jop ), the results are (31.23 , 22.76 , 19.61)% respectively.The person economic income is another important demographic factor that significantly affects persons according to their income, it is found that persons with low income are infected compared with those of high income.And it is found that the factor ( in the family arrested person ) is the most important factor for the transmission and prevalence of scabies between peoples, the ratio of infection is (27.12)% compared with another studied factor.